Meningkatkan Hasil Belajar Siswa Melalui Metode Mind Mapping Berbantukan Media Gambar SD Negeri 169 Tokala - Ratna Ratna; Muhammad Azis; Muhammad Fahreza (Universitas Negeri Surabaya, 2022)
This study aims to improve student learning outcomes through mind mapping methods assisted by image media at SD Negeri 169 Tokala. The type of research is classroom action. The research subjects were 20 class V students. Collecting data through observation and documentation tests. Data analysis used descriptive analysis. The results showed that there was completeness of student learning outcomes in each cycle, where the average student learning outcomes in cycle I and cycle II increased. Thus, it was concluded that the mind mapping method with the aid of image media could improve the learning outcomes of fifth graders at SD Negeri 169 Tokala